A method for preparing light-shielding coated textile with triple antibacterial effect

By modifying titanium dioxide particles with Fe3+/tannic acid/PEI/Lloyd's violet cross-links and applying them as a foamed coating, the fabric achieves triple antibacterial effects through light reflection, absorption, and sterilization, addressing the lack of effective antibacterial properties in existing light-shielding fabrics.

CN115976849BActive Publication Date: 2024-12-27ZHEJIANG DEYI SHADING TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211672981.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-26
Publication Date
2024-12-27
Estimated Expiration
2042-12-26

AI Technical Summary

Technical Problem

Existing light-shielding fabrics lack effective antibacterial properties and do not provide long-lasting protection against microorganisms, particularly under light conditions.

Method used

A method involving the modification of titanium dioxide particles with Fe3+/tannic acid/PEI/Lloyd's violet network cross-links, which are then mixed with polyacrylate emulsion and applied as a foamed coating to fabrics, leveraging light reflection, absorption, and photodynamic and photothermal sterilization for triple antibacterial effects.

Benefits of technology

The modified fabric achieves long-lasting antibacterial performance, inhibiting microorganism reproduction and killing them under light conditions, with polyamino groups in PEI, photodynamic effects from Lloyd's violet, and photothermal effects from tannic acid polymer, enhancing overall antibacterial efficacy.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a method for preparing a light-shielding coating textile with triple antibacterial effect, and belongs to the technical field of functional textile processing. 3+ complexation, laccase oxidation of phenolic hydroxyl groups to form quinone groups, self-crosslinking reaction of quinone groups with amino groups, and Fe 3+ / tannic acid polyphenol network, a structurally stable Fe 3+ / Tannic acid / PEI / Lloyd's purple / titanium dioxide functional particles. In the particles, titanium dioxide has a light reflection effect, tannic acid has a light absorption effect, PEI has an antibacterial effect, Lloyd's purple has a photodynamic bactericidal effect, and tannic acid polymer has a photothermal bactericidal effect. The new multifunctional titanium dioxide particles are mixed with polyacrylate emulsion to prepare a foaming slurry, which is applied to the surface of the fabric to prepare a light-shielding coating textile with triple antibacterial effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a method for preparing a light-shielding coating textile with triple antibacterial effects, belonging to the technical field of functional textile processing. Background Art

[0002] Blackout fabrics are widely used in home textiles and outdoors, and are often used in curtains, awnings, etc. In addition to home use, they are also often used in hotels, cinemas, large shopping malls and other places.

[0003] Light-shielding coated fabrics are coated on the surface of ordinary fabrics. Usually, light-shielding agents such as titanium dioxide, carbon black or other coatings are added to the coating agent. After multiple coatings, the light-shielding effect is achieved. When light is irradiated on the coating on the surface of the fabric, it is reflected or absorbed, and thus cannot pass through the fabric. At present, common coating methods for light-shielding fabrics include foam coating and transfer coating, among which foam coating is the most common.

[0004] Foam coating is a process of mechanically mixing the polymer forming the coating with air to form micropores in the coating. The foam micropores can give the coated fabric excellent light-shielding, heat-insulating, and thermal-keeping functions. Transfer coating is to apply the reflective coating agent to the release paper, then press it with the fabric, and finally transfer and bond it to the fabric.

[0005] The present invention establishes a method for preparing a light-shielding coating textile with triple antibacterial effects. The present invention (1) utilizes Fe 3+ (1) oxidize tannic acid with hydroxyl groups, amino groups in polyethyleneimine (PEI), and amino groups in Lloyd's purple; (2) oxidize tannic acid with laccase to convert the phenolic hydroxyl groups into quinones, which then react with amino groups in polyethyleneimine (PEI) and amino groups in Lloyd's purple through Michael addition and Schiff base reactions to form network crosslinks; (3) use Fe 3+ / tannic acid polyphenol network adhesive properties, the Fe formed by laccase oxidation 3+ / tannic acid / PEI / Lowry purple network cross-linked material, adhered and fixed on the surface of titanium dioxide particles; finally, Fe 3+ / Tannic acid / PEI / Lloyd's purple / titanium dioxide functional particles. In the particles, titanium dioxide has light reflection, tannic acid has light absorption, PEI has antibacterial effect (relying on polyamino sterilization), Lloyd's purple has photodynamic sterilization, and tannic acid polymer has photothermal sterilization. The new multifunctional titanium dioxide particles are mixed with polyacrylate emulsion to prepare foaming slurry, which is applied to the surface of fabrics to prepare a light-shielding coating textile with triple antibacterial effect.

[0006] At present, there are no reports of modified titanium dioxide particles with triple antibacterial effects at home or abroad, nor are there any reports of particles with similar structures being used for foam coating finishing of textiles. Summary of the invention

[0007] The present invention utilizes the catalytic oxidation of laccase, Fe 3+ The complexation of Fe 3+ / Adhesion properties of tannic acid polyphenol networks, modification of titanium dioxide particles to Fe in one step 3+ / tannic acid / PEI / Lowry's violet / titanium dioxide functional particles, wherein laccase catalyzes the oxidation of phenolic hydroxyl groups of tannic acid to quinones, which then react with amino groups of PEI and Lowry's violet to undergo Michael addition and Schiff base reactions; Fe 3+ A complex is formed between the phenolic hydroxyl group of tannic acid, PEI and the amino group of Lawrence Violet; Fe 3+ / Tannic acid / PEI / Law's purple network cross-linked compound is self-adhesive and fixed on the surface of titanium dioxide particles. Then, the modified titanium dioxide particles are mixed with polyacrylate emulsion, air is mixed into a foaming slurry, and the coating is applied to the surface of the fabric. The modified titanium dioxide particles have light reflection, tannic acid has light absorption, PEI has antibacterial effect (relying on polyamino sterilization), Law's purple has photodynamic sterilization (light produces active oxygen free radical sterilization), and tannic acid polymer has photothermal sterilization, thereby giving the fabric excellent antibacterial and light-shielding properties. In addition, it can be seen from the embodiments and comparative examples that Law's purple can improve the photothermal properties of modified titanium dioxide particles, and tannic acid can improve the photodynamic antibacterial properties of modified titanium dioxide particles, indicating that there is a synergistic effect between Law's purple and tannic acid. When the two are used together, the photodynamic and photothermal antibacterial properties of the particles are better than the antibacterial effects when they are used separately.

[0008] The specific process and steps are as follows:

[0009] (1) Fe 3+ / Tannic acid / PEI / Lloyd's violet / titanium dioxide functional particles preparation

[0010] In a pH 5-6 buffer solution, add laccase 0.05-0.5 g / L, tannic acid 1-5 g / L, PEI 0.5-2 g / L, Lloyd's violet 1-5 g / L, FeCl3 0.5-1 g / L, and titanium dioxide 50-200 g / L, then stir and react at 40-50 °C for 2-6 hours. After the reaction is completed, filter and dry to obtain Fe 3+ / Tannic acid / PEI / Lowe's violet / titanium dioxide functional particles.

[0011] (2) Fe 3+ Preparation of fabrics with foamed coatings of / tannic acid / PEI / Lowry's violet / titanium dioxide functional particles

[0012] Process prescription and conditions:

[0013] ① Weigh the Fe prepared in step (1) 3+ / tannic acid / PEI / Lloyd's purple / titanium dioxide functional particles 5-10 g / L, carbon black 1-5 g / L, polyacrylate slurry volume fraction 70%-85%, ammonium stearate emulsion volume fraction 2%-10%, add water to 100%, ammonia water to adjust pH 8-9, and obtain a black slurry;

[0014] ② The volume fraction of polyacrylate slurry is 70%~85%, the volume fraction of unmodified titanium dioxide slurry is 10~15%, the volume fraction of ammonium stearate emulsion is 2%~10%, water is added to 100%, and ammonia water is used to adjust the pH to 8~9 to obtain a white slurry;

[0015] ③ After the above slurry is foamed with a foaming ratio of 1:3~1:4, three layers of white color paste, black color paste and white color paste are applied on the surface of the fabric in the order of white color paste, black color paste and white color paste. After each coating, it is baked at 150~180℃ for 2~5 minutes to obtain a light-shielding coated textile with triple antibacterial effects of multi-amino antibacterial, photodynamic antibacterial and photothermal antibacterial.

[0016] A method for preparing a light-shielding coated textile with triple antibacterial effects, wherein the fabric suitable for treatment is selected from one of polyester fabric, cotton fabric and linen fabric; and the coating method is foaming coating.

[0017] Beneficial effects of the present invention:

[0018] The present invention has the following advantages:

[0019] The prepared Fe 3+ / Tannic acid / PEI / Lowe's violet / titanium dioxide functional particles are environmentally friendly finishing agents and have no adverse effects on human health and the environment;

[0020] Fe 3+ There are various cross-linking effects in the functional particles of / tannic acid / PEI / Lowry's violet / titanium dioxide, such as metal ion complexation, chemical cross-linking of amino and quinone groups, and a large number of hydrogen bond networks. These forces make tannic acid, PEI and Lowry's violet firmly bound to the surface of titanium dioxide particles, and also prevent these functional components from being released from the particles. The foaming coating of the functional particles is applied to the surface of the fabric to obtain a long-lasting antibacterial effect.

[0021] The prepared light-shielding coated textile has a triple antibacterial effect; the polyamino group in PEI enables the fabric to inhibit the reproduction of microorganisms on its surface in any state; the photodynamic antibacterial effect of Law's violet can enhance the antibacterial property of the fabric under light conditions, and the active oxygen free radicals it produces can kill microorganisms in the air around the fabric; the photothermal effect of tannic acid polymer can further enhance the antibacterial performance of the fabric surface under light conditions. Under the above triple antibacterial effect, Fe 3+ / Tannin acid / PEI / Lowry violet / titanium dioxide functional particle foamed coating fabric has excellent antibacterial properties. DETAILED DESCRIPTION Example

[0022] Sample type: polyester woven fabric

[0023] (1) Fe 3+ / Tannic acid / PEI / Lloyd's violet / titanium dioxide functional particles preparation

[0024] In a pH 5.5 buffer solution, 0.2 g / L laccase, 2 g / L tannic acid, 2 g / L PEI, 2 g / L Lloyd's violet, 0.5 g / L FeCl3, and 100 g / L titanium dioxide were added, and then stirred at 40 °C for 5 hours. After the reaction, the Fe 3+ / Tannic acid / PEI / Lowe's violet / titanium dioxide functional particles.

[0025] (2) Fe 3+ Preparation of fabrics with foamed coatings of / tannic acid / PEI / Lowry's violet / titanium dioxide functional particles

[0026] Process prescription and conditions:

[0027] ① Weigh the Fe prepared in step (1) 3+ / tannic acid / PEI / Lloyd's purple / titanium dioxide functional particles 10 g / L, carbon black 3 g / L, polyacrylate slurry volume fraction 70%, ammonium stearate emulsion volume fraction 5%, add water to 100%, ammonia water to adjust pH 8, to obtain a black slurry;

[0028] ② The volume fraction of polyacrylate slurry is 80%, the volume fraction of unmodified titanium dioxide slurry is 10%, and the volume fraction of ammonium stearate emulsion is 5%. Water is added to 100%, and ammonia water is used to adjust the pH to 8 to obtain a white slurry;

[0029] ③ After the above slurry is foamed (foaming ratio 1:3), three layers of white color paste, black color paste and white color paste are coated on the surface of the polyester fabric in the order of white color paste, black color paste and white color paste. After each coating, it is baked at 150°C for 5 minutes to obtain a light-shielding coated polyester fabric with triple antibacterial effects of multi-amino antibacterial, photodynamic antibacterial and photothermal antibacterial.

[0030] Sample 1: untreated polyester woven fabric;

[0031] Sample 2: The antibacterial and light-shielding polyester woven fabric was obtained through the above steps (1) and (2).

[0032] Using the test of "GB / T20944.3-2008 Evaluation of antibacterial properties of textiles Part 3: Oscillation method", sample 1 has no antibacterial performance, sample 2 has an antibacterial rate of 100% against Staphylococcus aureus and 100% against Escherichia coli. After 50 washes, the antibacterial rate against Staphylococcus aureus is 98% and the antibacterial rate against Escherichia coli is 99%.

[0033] Under sunlight conditions, drop bacterial liquid (Staphylococcus aureus, Escherichia coli) on the surface of the test sample, wash off the bacteria on the sample surface after 10 minutes, and calculate the sterilization rate. Sample 1 has no sterilization performance, while sample 2 has a sterilization rate of 99% for Staphylococcus aureus and 99% for Escherichia coli. After washing the sample 50 times, perform light sterilization test again. Sample 1 has no sterilization performance, while sample 2 has a sterilization rate of 90% for Staphylococcus aureus and 90% for Escherichia coli.

[0034] The light transmittance of sample 1 is 50%, and the light transmittance of sample 2 is 1%. Example

[0035] Sample type: pure cotton woven fabric

[0036] (1) Fe 3+ / Tannic acid / PEI / Lloyd's violet / titanium dioxide functional particles preparation

[0037] In a pH 6 buffer solution, 0.5 g / L laccase, 5 g / L tannic acid, 2 g / L PEI, 5 g / L Lloyd's violet, 1 g / L FeCl3, and 200 g / L titanium dioxide were added, and then stirred at 50 °C for 6 hours. After the reaction, the Fe 3+ / Tannic acid / PEI / Lowe's violet / titanium dioxide functional particles.

[0038] (2) Fe 3+ Preparation of fabrics with foamed coatings of / tannic acid / PEI / Lowry's violet / titanium dioxide functional particles

[0039] Process prescription and conditions:

[0040] ① Weigh the Fe prepared in step (1) 3+ / tannic acid / PEI / Lloyd's purple / titanium dioxide functional particles 10 g / L, carbon black 3 g / L, polyacrylate slurry volume fraction 80%, ammonium stearate emulsion volume fraction 10%, add water to 100%, ammonia water to adjust pH 8.5, to obtain a black slurry;

[0041] ② The volume fraction of polyacrylate slurry is 85%, the volume fraction of unmodified titanium dioxide slurry is 10%, the volume fraction of ammonium stearate emulsion is 3%, water is added to 100%, and ammonia water is used to adjust the pH to 9 to obtain a white slurry;

[0042] ③ After the above slurry is foamed (foaming ratio 1:4), three layers of white color paste, black color paste and white color paste are coated on the surface of pure cotton woven fabric in the order of white color paste, black color paste and white color paste. After each coating, it is baked at 180°C for 2 minutes to obtain a light-shielding coated pure cotton fabric with triple antibacterial effects of multi-amino antibacterial, photodynamic antibacterial and photothermal antibacterial.

[0043] Sample 3: untreated pure cotton woven fabric;

[0044] Sample 4: After the above steps (1) and (2), an antibacterial and light-shielding pure cotton woven fabric is obtained.

[0045] Using the test of "GB / T20944.3-2008 Evaluation of antibacterial properties of textiles Part 3: Oscillation method", sample 3 has no antibacterial performance, sample 4 has an antibacterial rate of 100% against Staphylococcus aureus and 100% against Escherichia coli. After 50 washes, the antibacterial rates against Staphylococcus aureus and Escherichia coli are 99% and 99% respectively.

[0046] Under sunlight conditions, bacterial liquid (Staphylococcus aureus, Escherichia coli) was dripped on the surface of the test sample, and the bacteria on the surface of the sample were washed off after 10 minutes, and the sterilization rate was calculated. Sample 3 had no sterilization performance, and sample 4 had a sterilization rate of 98% for Staphylococcus aureus and 98% for Escherichia coli. After the sample was washed 50 times, it was tested for light sterilization. Sample 3 had no sterilization performance, and sample 4 had a sterilization rate of 92% for Staphylococcus aureus and 88% for Escherichia coli.

[0047] The transmittance of sample 3 is 60%, and the transmittance of sample 4 is 1%.

[0048] Comparative Example 1 Omitting Tannic Acid

[0049] Compared with Sample 2 in Example 1, tannic acid is omitted. A method for preparing a light-shielding coated polyester fabric with antibacterial effect comprises the following steps:

[0050] (1) Fe 3+ / PEI / Lloyd's Purple / TiO2 Functional Particle Preparation

[0051] In a pH 5.5 buffer solution, 0.2 g / L laccase, 2 g / L PEI, 2 g / L Lloyd's violet, 0.5 g / L FeCl3, and 100 g / L titanium dioxide were added, and then stirred at 40 °C for 5 hours. After the reaction, the Fe 3+ / PEI / Lowry Violet / Titanium dioxide functional particles.

[0052] (2) Fe 3+ Preparation of Foamed Coated Fabrics with PEI / Lloyd's Purple / TiO2 Functional Particles

[0053] Process prescription and conditions:

[0054] ① Weigh the Fe prepared in step (1) 3+ / PEI / Lowry Purple / titanium dioxide functional particles 10 g / L, carbon black 3 g / L, polyacrylate slurry volume fraction 70%, ammonium stearate emulsion volume fraction 5%, add water to 100%, ammonia water to adjust pH 8, and obtain black slurry;

[0055] ② The volume fraction of polyacrylate slurry is 80%, the volume fraction of unmodified titanium dioxide slurry is 10%, and the volume fraction of ammonium stearate emulsion is 5%. Water is added to 100%, and ammonia water is used to adjust the pH to 8 to obtain a white slurry;

[0056] ③ After the above slurry is foamed (foaming ratio 1:3), three layers of white color paste, black color paste and white color paste are coated on the surface of the polyester fabric in the order of white color paste, black color paste and white color paste. After each coating, it is baked at 150°C for 5 minutes to obtain a light-shielding coated polyester fabric with antibacterial effect.

[0057] Sample 5: The antibacterial and light-shielding polyester woven fabric was obtained through the above steps (1) and (2).

[0058] Using the test of "GB / T20944.3-2008 Evaluation of antibacterial properties of textiles Part 3: Oscillation method", sample 5 has an antibacterial rate of 100% against Staphylococcus aureus and 100% against Escherichia coli. After 50 washes, the antibacterial rate against Staphylococcus aureus is 95% and the antibacterial rate against Escherichia coli is 95%.

[0059] Under sunlight conditions, drop bacterial liquid (Staphylococcus aureus, Escherichia coli) on the surface of the test sample, wash off the bacteria on the sample surface after 10 minutes, and calculate the sterilization rate. Sample 5 has a sterilization rate of 80% against Staphylococcus aureus and 78% against Escherichia coli. After washing the sample 50 times, perform light sterilization test again. Sample 5 has a sterilization rate of 50% against Staphylococcus aureus and 40% against Escherichia coli.

[0060] Compared with sample 2, after omitting tannic acid, the bactericidal performance of sample 5 under 10-min light irradiation conditions decreased, indicating that tannic acid is a key component of light sterilization.

[0061] Comparative Example 2 Omitting Lloyd's Purple

[0062] Compared with Sample 2 in Example 1, Lloyd's Purple is omitted. A method for preparing a light-shielding coated polyester fabric with antibacterial effect comprises the following steps:

[0063] (1) Fe 3+ / Tannic acid / PEI / TiO2 functional particles preparation

[0064] Laccase 0.2 g / L, tannic acid 2 g / L, PEI 2 g / L, FeCl3 0.5 g / L, titanium dioxide 100 g / L were added to the pH 5.5 buffer solution, and then stirred at 40 °C for 5 hours. After the reaction, the Fe 3+ / Tannic acid / PEI / titanium dioxide functional particles.

[0065] (2) Fe 3+ Preparation of fabrics with foamed coatings of / tannic acid / PEI / titanium dioxide functional particles

[0066] Process prescription and conditions:

[0067] ① Weigh the Fe prepared in step (1) 3+ / tannic acid / PEI / titanium dioxide functional particles 10 g / L, carbon black 3 g / L, polyacrylate slurry volume fraction 70%, ammonium stearate emulsion volume fraction 5%, add water to 100%, ammonia water to adjust pH 8, to obtain a black slurry;

[0068] ② The volume fraction of polyacrylate slurry is 80%, the volume fraction of unmodified titanium dioxide slurry is 10%, and the volume fraction of ammonium stearate emulsion is 5%. Water is added to 100%, and ammonia water is used to adjust the pH to 8 to obtain a white slurry;

[0069] ③ After the above slurry is foamed (foaming ratio 1:3), three layers of white color paste, black color paste and white color paste are coated on the surface of the polyester fabric in the order of white color paste, black color paste and white color paste. After each coating, it is baked at 150°C for 5 minutes to obtain a light-shielding coated polyester fabric with antibacterial effect.

[0070] Sample 6: Antibacterial and light-shielding polyester woven fabric is obtained through the above steps (1) and (2).

[0071] Using the test of "GB / T20944.3-2008 Evaluation of antibacterial properties of textiles Part 3: Oscillation method", sample 6 has an antibacterial rate of 100% against Staphylococcus aureus and 100% against Escherichia coli. After 50 washes, the antibacterial rate against Staphylococcus aureus is 95%, and the antibacterial rate against Escherichia coli is 95%.

[0072] Under sunlight conditions, drop bacterial liquid (Staphylococcus aureus, Escherichia coli) on the surface of the test sample, wash off the bacteria on the sample surface after 10 minutes, and calculate the sterilization rate. Sample 6 has a sterilization rate of 60% against Staphylococcus aureus and 55% against Escherichia coli. After washing the sample 50 times, the light sterilization test was carried out again. The sterilization rate of sample 6 against Staphylococcus aureus was 26%, and the sterilization rate against Escherichia coli was 22%.

[0073] Compared with Sample 2, after omitting Lloyd's violet, the bactericidal performance of Sample 6 under 10 minutes of light exposure decreased; compared with Sample 5, omitting Lloyd's violet had a greater impact on the photothermal bactericidal performance of the fabric than omitting tannic acid, which also shows that Lloyd's violet is a key component of light sterilization and is more important than tannic acid.

[0074] Comparative Example 3 Omitting Polyethyleneimine (PEI)

[0075] Compared with Sample 2 in Example 1, polyethyleneimine (PEI) is omitted. A method for preparing a light-shielding coated polyester fabric with antibacterial effect comprises the following steps:

[0076] (1) Fe 3+ / Tannic acid / Low's violet / Titanium dioxide functional particles preparation

[0077] In a pH 5.5 buffer solution, 0.2 g / L laccase, 2 g / L tannic acid, 2 g / L Lloyd's violet, 0.5 g / L FeCl3, and 100 g / L titanium dioxide were added, and then stirred at 40 °C for 5 hours. After the reaction was completed, the Fe 3+ / Tannic acid / Law's violet / titanium dioxide functional particles.

[0078] (2) Fe 3+ Preparation of foamed coating fabric with / tannic acid / Low's violet / titanium dioxide functional particles

[0079] Process prescription and conditions:

[0080] ① Weigh the Fe prepared in step (1) 3+ / tannic acid / Lowe's purple / titanium dioxide functional particles 10 g / L, carbon black 3g / L, polyacrylate slurry volume fraction 70%, ammonium stearate emulsion volume fraction 5%, add water to 100%, ammonia water to adjust pH 8, to obtain a black slurry;

[0081] ② The volume fraction of polyacrylate slurry is 80%, the volume fraction of unmodified titanium dioxide slurry is 10%, and the volume fraction of ammonium stearate emulsion is 5%. Water is added to 100%, and ammonia water is used to adjust the pH to 8 to obtain a white slurry;

[0082] ③ After the above slurry is foamed (foaming ratio 1:3), three layers of white color paste, black color paste and white color paste are coated on the surface of the polyester fabric in the order of white color paste, black color paste and white color paste. After each coating, it is baked at 150°C for 5 minutes to obtain a light-shielding coated polyester fabric with antibacterial effect.

[0083] Sample 7: The antibacterial and light-shielding polyester woven fabric was obtained through the above steps (1) and (2).

[0084] Using the test of "GB / T20944.3-2008 Evaluation of antibacterial properties of textiles Part 3: Oscillation method", sample 7 had an antibacterial rate of 40% against Staphylococcus aureus and 35% against Escherichia coli. After 50 washes, there was no antibacterial effect on Staphylococcus aureus and Escherichia coli.

[0085] Under sunlight conditions, bacterial liquid (Staphylococcus aureus, Escherichia coli) was dripped on the surface of the test sample, and the bacteria on the surface of the sample were washed off after 10 minutes, and the sterilization rate was calculated. The sterilization rate of sample 7 against Staphylococcus aureus was 45%, and the sterilization rate against Escherichia coli was 30%. After the sample was washed 50 times, it was tested for light sterilization. Sample 7 had no sterilization effect on Staphylococcus aureus and Escherichia coli.

[0086] Compared with Sample 2, Sample 5 and Sample 6, after omitting polyethyleneimine (PEI), the antibacterial and bactericidal abilities of Sample 7 decreased significantly.

[0087] First, in the test of "GB / T20944.3-2008 Evaluation of Antibacterial Properties of Textiles Part 3: Oscillation Method", the antibacterial rate of sample 7 is only 40%, far lower than 100% when PEI is added. This shows that PEI plays a key role in the long-term antibacterial effect of antibacterial shading fabrics.

[0088] Secondly, after omitting polyethyleneimine (PEI), the light sterilization performance of sample 7 also dropped significantly. Although PEI does not have photothermal sterilization ability, it is a key component of the PEI / tannic acid / Law's purple network cross-linking. Without PEI, tannic acid and Law's purple are difficult to cross-link and fix to titanium dioxide particles in large quantities, so the light sterilization ability of sample 7 is greatly reduced.

[0089] Comparative Example 4 Omitting FeCl3

[0090] Compared with Sample 2 in Example 1, FeCl3 is omitted. A method for preparing a light-shielding coated polyester fabric with antibacterial effect comprises the following steps:

[0091] (1) Preparation of tannic acid / PEI / Lowry violet / titanium dioxide functional particles

[0092] In a pH 5.5 buffer solution, 0.2 g / L laccase, 2 g / L tannic acid, 2 g / L PEI, 2 g / L Lloyd's violet, and 100 g / L titanium dioxide were added, and then stirred for reaction at 40 °C for 5 hours. After the reaction, the particles were filtered and dried to obtain tannic acid / PEI / Lloyd's violet / titanium dioxide functional particles.

[0093] (2) Preparation of tannic acid / PEI / Lloyd's violet / titanium dioxide functional particle foaming coating fabric

[0094] Process prescription and conditions:

[0095] ① Weigh 10 g / L of the tannic acid / PEI / Low's violet / titanium dioxide functional particles prepared in step (1), 3 g / L of carbon black, 70% by volume of polyacrylate slurry, and 5% by volume of ammonium stearate emulsion, add water to 100%, and adjust the pH to 8 with ammonia water to obtain a black slurry;

[0096] ② The volume fraction of polyacrylate slurry is 80%, the volume fraction of unmodified titanium dioxide slurry is 10%, and the volume fraction of ammonium stearate emulsion is 5%. Water is added to 100%, and ammonia water is used to adjust the pH to 8 to obtain a white slurry;

[0097] ③ After the above slurry is foamed (foaming ratio 1:3), three layers of white color paste, black color paste and white color paste are coated on the surface of the polyester fabric in the order of white color paste, black color paste and white color paste. After each coating, it is baked at 150°C for 5 minutes to obtain a light-shielding coated polyester fabric with antibacterial effect.

[0098] Sample 8: The antibacterial and light-shielding polyester woven fabric was obtained through the above steps (1) and (2).

[0099] Using the test of "GB / T20944.3-2008 Evaluation of antibacterial properties of textiles Part 3: Oscillation method", sample 8 has an antibacterial rate of 98% against Staphylococcus aureus and 99% against Escherichia coli. After 50 washes, the antibacterial rate against Staphylococcus aureus is 80% and the antibacterial rate against Escherichia coli is 75%.

[0100] Under sunlight conditions, drop bacterial liquid (Staphylococcus aureus, Escherichia coli) on the surface of the test sample, wash off the bacteria on the sample surface after 10 minutes, and calculate the sterilization rate. Sample 8 has a sterilization rate of 92% for Staphylococcus aureus and 90% for Escherichia coli. After washing the sample 50 times, perform light sterilization test again. Sample 8 has a sterilization rate of 82% for Staphylococcus aureus and 85% for Escherichia coli.

[0101] Compared with sample 2, after omitting FeCl3, the antibacterial and bactericidal abilities of sample 8 decreased slightly. 3+ The metal ion complexation in Fe 3+ / tannic acid / PEI / Lloyd's violet / titanium dioxide functional particles play a certain role. 3+ The metal ion complexation of tannic acid and the cross-linking of the quinone group of PEI and the amino group of Lawrence purple together constructed a structurally stable Fe 3+ / Tannic acid / PEI / Lowe's violet / titanium dioxide functional particles.

[0102] Comparative Example 5 Omitting Laccase

[0103] Compared with Sample 2 in Example 1, laccase is omitted. A method for preparing a light-shielding coated polyester fabric with antibacterial effect comprises the following steps:

[0104] (1) Fe 3+ / Tannic acid / PEI / Lloyd's violet / titanium dioxide functional particles preparation

[0105] In a pH 5.5 buffer solution, 2 g / L tannic acid, 2 g / L PEI, 2 g / L Lloyd's violet, 0.5 g / L FeCl3, and 100 g / L titanium dioxide were stirred at 40 °C for 5 hours. After the reaction, the Fe 3+ / Tannic acid / PEI / Lowe's violet / titanium dioxide functional particles.

[0106] (2) Fe 3+ Preparation of fabrics with foamed coatings of / tannic acid / PEI / Lowry's violet / titanium dioxide functional particles

[0107] Process prescription and conditions:

[0108] ① Weigh the Fe prepared in step (1) 3+ / tannic acid / PEI / Lloyd's purple / titanium dioxide functional particles 10 g / L, carbon black 3 g / L, polyacrylate slurry volume fraction 70%, ammonium stearate emulsion volume fraction 5%, add water to 100%, ammonia water to adjust pH 8, to obtain a black slurry;

[0109] ② The volume fraction of polyacrylate slurry is 80%, the volume fraction of unmodified titanium dioxide slurry is 10%, and the volume fraction of ammonium stearate emulsion is 5%. Water is added to 100%, and ammonia water is used to adjust the pH to 8 to obtain a white slurry;

[0110] ③ After the above slurry is foamed (foaming ratio 1:3), three layers of white color paste, black color paste and white color paste are coated on the surface of the polyester fabric in the order of white color paste, black color paste and white color paste. After each coating, it is baked at 150°C for 5 minutes to obtain a light-shielding coated polyester fabric with antibacterial effect.

[0111] Sample 9: The antibacterial and light-shielding polyester woven fabric was obtained through the above steps (1) and (2).

[0112] Using the test of "GB / T20944.3-2008 Evaluation of antibacterial properties of textiles Part 3: Oscillation method", sample 9 has an antibacterial rate of 90% against Staphylococcus aureus and 92% against Escherichia coli. After 50 washes, the antibacterial rate against Staphylococcus aureus is 60% and the antibacterial rate against Escherichia coli is 50%.

[0113] Under sunlight conditions, bacterial liquid (Staphylococcus aureus, Escherichia coli) was dripped on the surface of the test sample, and the bacteria on the surface of the sample were washed off after 10 minutes, and the sterilization rate was calculated. Sample 9 had a sterilization rate of 85% for Staphylococcus aureus and 70% for Escherichia coli. After the sample was washed 50 times, it was tested for light sterilization. Sample 9 had no sterilization effect on Staphylococcus aureus and Escherichia coli.

[0114] Compared with sample 2, after laccase was omitted, the antibacterial and bactericidal abilities of sample 9 decreased, especially after 50 washes, the antibacterial and light bactericidal activities of sample 9 decreased significantly. This indicates that laccase oxidizes tannic acid to form quinone groups, which then undergo covalent cross-linking reaction with PEI and Lloyd's violet, which is the key to the firm binding of PEI and Lloyd's violet to titanium dioxide particles.

Claims

1. A method for preparing a light-shielding coated textile with triple antibacterial effect, characterized in that: The specific steps are as follows: (1) Fe 3+ / Tannic acid / PEI / Lloyd's violet / titanium dioxide functional particles preparation In a pH 5-6 buffer solution, add laccase 0.05-0.5 g / L, tannic acid 1-5 g / L, PEI 0.5-2 g / L, Lloyd's violet 1-5 g / L, FeCl3 0.5-1 g / L, and titanium dioxide 50-200 g / L, then stir and react at 40-50 °C for 2-6 hours. After the reaction is completed, filter and dry to obtain Fe 3+ / Tannic acid / PEI / Law's violet / titanium dioxide functional particles; (2) Fe 3+ Preparation of fabrics with foamed coatings of / tannic acid / PEI / Lowry's violet / titanium dioxide functional particles Process prescription and conditions: ① Weigh the Fe prepared in step (1) 3+ / tannic acid / PEI / Lloyd's purple / titanium dioxide functional particles 5-10 g / L, carbon black 1-5 g / L, polyacrylate slurry volume fraction 70%-85%, ammonium stearate emulsion volume fraction 2%-10%, add water to 100%, ammonia water to adjust pH 8-9, and obtain a black slurry; ② The volume fraction of polyacrylate slurry is 70%~85%, the volume fraction of unmodified titanium dioxide slurry is 10~15%, the volume fraction of ammonium stearate emulsion is 2%~10%, water is added to 100%, and ammonia water is used to adjust the pH to 8~9 to obtain a white slurry; ③ After the above slurry is foamed with a foaming ratio of 1:3~1:4, three layers of white color paste, black color paste and white color paste are applied on the surface of the fabric in the order of white color paste, black color paste and white color paste. After each coating, it is baked at 150~180℃ for 2~5 minutes to obtain a light-shielding coated textile with triple antibacterial effects of multi-amino antibacterial, photodynamic antibacterial and photothermal antibacterial.

2. The method for preparing a light-shielding coated textile with triple antibacterial effect according to claim 1, characterized in that: The fabric suitable for treatment is selected from polyester fabric, cotton fabric and linen fabric.

3. The method for preparing a light-shielding coated textile with triple antibacterial effect according to claim 1, characterized in that: The coating method is foaming coating.